Perlakuan Defoliasi untuk Meningkatkan Pembentukan dan Pertumbuhan Cabang Lateral Jarak Pagar (Jatropha curcas) - Darmanti, Sri; Setiari, Nintya; Romawati, Tanti Dwi (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2008)
Jatropha is an alternative resource of sustainable energi. Therefore, to support the use of sustainable energi,an increase production of Jatropha seed is important. As Jatropha seeds (fruits) only growth at terminal andaxial bud, therefore the presence of lateral bud is necessary to increase production of Jatropha seed.Formation of lateral bud is affected by the balance between auxin and sitokinin. Defoliation will control thebalance of these two hormone. In this study, defoliation is conducted on seedling at the age of 4 month.Each treatment was replicated Â  Â 7 times. Variabel were observed and ended after 6 month. Result indicatecthat either defoliation will stimulated the formation and growth of lateral bud.